TRIBOLOGICAL Sl1JDY OF JATROPHA (Jatropha carcass L) OIL AS ECO-FRIENDL Y BOUNDARY LUBRICANT - SYAH LUBIS, ABDUL MUNIR HIDAYAT (2013)
The prospect of jatropha oil as lubricant oil for boundary lubrication application is still not much studied yet. This research is mainly focused on enhancement of tribological properties ofjatropha oil as ceo-friendly lubricant base stock. The work is involving study on the effect of structural modification and additives addition to tribological properties of jatropha oil. The objectives of the research are: (i) to investigate friction, wear. and oxidation of jatropha oil, (ii) to synthesize and investigate friction, wear, and oxidation of jatropha oil derivatives, and (iii) to investigate the effects of anti-wear and antioxidant additives on friction, wear and oxidation of jatropha oil. Friction and wear preventive properties of the oil were examined by four ball method. Thermo-oxidative property of the oil was studied by thermo-gravimetric analysis (TGA) method. Fourier transform infra-red (FTIR) and nuclear magnetic resonance (NMR) were employed to study functional groups and stmcture changes in the jatropha oil.